Analisis Dampak Bencana Banjir terhadap Kondisi Sosial dan Ekonomi pada Masyarakat - Sarifah, Fitriana; Arashi, Fahreza Bagus; Iskandar, Ayunda Lestari; Ramadhan, Moh. Azril Ridho; Daniswara, Muhamad Prama; Rahmadhani, Fatur (Universitas Sulawesi Barat, 2024)
Flooding is a natural phenomenon that occurs due to abundant water and overflows into land areas that are usually dry. The purpose of this research is to analyze the impact and factors that influence flood disasters on the social and economic conditions of the community to the handling and prevention of floods in general. This research will use a qualitative method approach with document analysis techniques. The method requires a systematic approach to records or documents as data sources. The results of this research are the social impact of flooding, including the need for people to evacuate to disturbed health including the obstruction of daily activities. The economic impact of flooding is crop failure, infrastructure damage, and disrupted business. The influencing factors are natural factors such as rising sea water, inadequate facilities and infrastructure such as poor drainage, to community activities and awareness such as littering. The handling and prevention of flood disasters is the need for spatial governance and infrastructure improvement as well as rehabilitation of forest and land functions.